(untitled) (Bangladesh Journal of Agricultural Research, 2017)
The experiment was conducted in a vinylhouse at the Banghabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh during January to May, 2012 to evaluate the effect of salt and water stress on gas exchange characters, dry matter production and K+/Na+ ions selectivity in three selected soybean genotypes, namely Galarsum, BD 2331 and BARI Soybean-6. The genotypes were exposed to six treatments viz. (i) control (tap water), (ii) water shortage (irrigation with 70% depletion of available soil water when leaf began to wilt at 10:00 am), (iii) 50 mM NaCl irrigation, (iv) 50 mM NaCl irrigation + water shortage, (v) 75 mM NaCl irrigation, and (vi) 75 mM NaCl irrigation + water shortage conditions. The results revealed that 75 mM NaCl salt + water stress treatment drastically reduced stomatal conductance, photosynthesis and transpiration rate irrespective of soybean genotypes. However, the genotype Galarsum showed minimum transpiritional water loss (1.45 mmol H2O m-2 s-1) and maximum photosynthesis (20.45 μmol CO2 m-2 s-1) as compared to BD 2331 and BARI Soybean-6 under 75 mM NaCl salt + water stress condition. Combined salt and water stress caused greater inhibition of shoot growth than either of the two in soybean. The shoot dry weights were decreased to 24.58, 23.00 and 21.57% of the control in Galarsum, BD 2331 and BARI Soybean-6, respectively at 75 mM NaCl salt + water stress. The genotype Galarsum accumulated higher amount of K+ (1.19%) and lower amount of Na+ ( 0.11%) in leaf tissue under 75 mM NaCl salt + water stress. Results indicated that the genotype Galarsum was more capable to cope with the high levels of salt under water stress condition than the other two genotypes. Bangladesh J. Agril. Res. 42(3): 487-501, September 2017